The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1460-9592.2012.03889.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound compared to age‐related formulas for uncuffed endotracheal intubation in a pediatric population

Abstract: Measuring MTDSA by ultrasound facilitates selection of the appropriate ETT in pediatric patients and may reduce the number of reintubations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
94
5
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(120 citation statements)
references
References 19 publications
5
94
5
16
Order By: Relevance
“…In a pilot study, role of ultrasound and its usefulness in predicting the tracheal diameter in paediatric patients were studied. 5 In the study, a prospective clinical study like the pilot study showed a higher correlation between ETT used clinically and ETT determined by ultrasound than between ETT used clinically and ETT determined by age based formula. With the aid of ultrasonography we could measure the air-column width at the level of the cricoid and select the optimal sized ETT for intubation in less than 2 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a pilot study, role of ultrasound and its usefulness in predicting the tracheal diameter in paediatric patients were studied. 5 In the study, a prospective clinical study like the pilot study showed a higher correlation between ETT used clinically and ETT determined by ultrasound than between ETT used clinically and ETT determined by age based formula. With the aid of ultrasonography we could measure the air-column width at the level of the cricoid and select the optimal sized ETT for intubation in less than 2 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies shows that the rate of agreement of age-based ETT size selection using the Cole formula is as low as 47-77. 5 Height-based technique such as Broselow tape can be used to compensate for individual variation in growth. However, these methods have many limitations because these formulas cannot consider variation in the growth of various internal organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of USG to predict appropriate ETT size in children has been previously studied (6)(7)(8)(9). These studies differ from each other, as shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Visualisation of the paediatric subglottic airway diameter by ultrasonography (USG) can enable a practitioner to better predict ETT size, preventing unnecessary tube changes and airway trauma. Several studies have investigated ideal cuffed tube size selection in paediatric patients; however, all these studies, including those where ultrasonographic measurements were performed (6)(7)(8)(9), selected the initial ETT size according to age-based formulas. However, other than Bae et al (6), who investigated uncuffed tube size, none of these studies actually involved initial placement of an ETT according to ultrasonographic measurements.…”
Section: Introductionmentioning
confidence: 99%